La eficiencia en la distribución y ventas y su efecto en la rentabilidad de la distribuidora de consumo masivo “Delgado” en el cantón El Empalme, año 2015 - Mariño Guime, Katherine Maribel (2015)
The study raised was done with the aim of analyzing the efficiency of sales and distribution and its effect on the profitability of the distributor "Slim" in the village of El Empalme, should determine the level of efficiency with which the process is performed distribution and sales. Therefore this work is absolutely justified by the need to correct deficiencies in the mechanisms of distribution and sales, optimizing resources, minimizing costs, implementing systems that enable the efficient development of logistics and sales in order to generate more useful to the company. To accomplish this research different methods that allowed capture the necessary data was applied a questionnaire that was applied to customers of the company to meet the preference of sales systems, frequency of orders, delivery times was prepared, and the various shortcomings that are made in the logistics system. Plus an interview with the owner to extract data on the investment in the distribution system, sales systems, sales and distribution policy and distribution routes by the company. The data obtained through the research show an efficiency ratio of the self-sales and pre 1,06 0,92 with a yield of 6% -8% correspondingly, which allowed propose a model of efficiency that allows optimize and minimize costs to solve the problems that hurt the company. The model is directed towards the automation of sales and distribution processes that allows for the marketing of products quickly and organized.